Effectiveness of acupuncture, ozonio therapy and low-intensity laser in the treatment of temporomandibular dysfunction of muscle origin: a randomized controlled trial - Síglia Adriana Campos TORTELLI; Leonardo SARAIVA; Daniela Cristina MIYAGAKI (Universidade Estadual Paulista, 2020)
Abstract Introduction One of the most common causes of orofacial pain is temporomandibular disorder (TMD). Objective The aim of this study was to compare the effectiveness of acupuncture, ozone therapy and laser therapy in the treatment of muscle TMD patients through a randomized controlled trial. Material and method Twelve professors and postgraduate students from the University of Passo Fundo, diagnosed with TMD, aged between 23 and 50 years old, of both sexes, were evaluated. Individuals were randomly divided into 3 groups: G1: laser therapy, G2: acupuncture, and G3: ozone therapy. TMD diagnostic questionnaires (RDC / TMD), Quality of Life Questionnaire (OHIP-14), Pain Scale (VAS) and maximum mouth opening were applied. Descriptive statistics and percentage were used for sample characterization, which were presented using absolute and relative frequency distributions. Qualitative variables were analyzed with Wilcoxon tests p≤0.05. Result There was no statistically significant difference between treatments. Regarding pain and maximum mouth opening, the groups showed no statistical difference when individually analyzed, but when compared in general, they did (p=0.002 and p=0.003). Conclusion It can be considered that all treatments were able to decrease pain and improve maximal opening capacity related to muscle TMD. It can also be concluded that the TMD-related quality of life, in relation to the pain variable, was generally effective when compared before and after the interventions.